2013
DOI: 10.4103/0970-2113.110417
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests in type 2 diabetes mellitus and their association with glycemic control and duration of the disease

Abstract: Background:Pulmonary complications of diabetes mellitus (DM) have been poorly characterized. Some authors have reported normal pulmonary functions and even concluded that spirometry is not at all necessary in diabetic patients. Some studies have shown abnormal respiratory parameters in patients of DM. Moreover, the duration of DM and glycemic control have varied impact on the pulmonary functions.Aims and Objectives:The study was undertaken to analyze the pulmonary function parameters in diabetic patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 25 publications
6
46
0
3
Order By: Relevance
“…India [6][7][8][9]. The wide range of geographical and climatic conditions in a large country such as India may be associated with regional differences in lung function.…”
Section: Discussionmentioning
confidence: 99%
“…India [6][7][8][9]. The wide range of geographical and climatic conditions in a large country such as India may be associated with regional differences in lung function.…”
Section: Discussionmentioning
confidence: 99%
“…A growing mass of data indicates a correlation of diabetes mellitus with lung dysfunction (6,7,8). Previous experimental studies have reported that diabetes attenuates the bronchomotor response as a result of decrease in sensory neuropeptide release (9).…”
Section: Introductionmentioning
confidence: 99%
“…glycosylation of the connective tissues, reduced pulmonary elastic recoil, increased muscle weakness and/or inflammation), which can result in restrictive alterations. In this regard, studies have demonstrated that pulmonary function tests are significantly decreased in subjects with T2DM in comparison to healthy controls [18,19,20]; this might be the result of direct exposure to elevated blood sugar [21,22] (table 1). In line with this, it was reported that metabolic syndrome, insulin resistance and systemic inflammation constitute important risk factors for reduced lung function in healthy, nonsmoking subjects [23], which suggest that even in the absence of smoking, diabetes can lead to similar effects on pulmonary function.…”
Section: The Adverse Effects Of Hyperglycemia On Lung Functionmentioning
confidence: 99%